2000
DOI: 10.1509/jmkg.64.2.35.18001
|View full text |Cite
|
Sign up to set email alerts
|

Corridors of Influence in the Dissemination of Customer-Oriented Strategy to Customer Contact Service Employees

Abstract: It is widely held that a customer-oriented firm is more likely to deliver exceptional service quality and create satisfied customers. However, little research has addressed the question of how the orientation can be disseminated among employees throughout the firm. This dissemination is especially important in service firms in which frontline, customer contact employees are responsible for translating a customer-oriented strategy into quality service. The authors propose a structural model that explains how se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
474
1
17

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(507 citation statements)
references
References 66 publications
(160 reference statements)
15
474
1
17
Order By: Relevance
“…The fact that the individuals in the sample have different occupations contributes to the generalisation of the findings and is coherent with other studies in the literature (e.g. De Jong, De Ruyter, & Lemmink, 2004;Hartline et al, 2000). We received 255 questionnaires back, of which 234 were usable, yielding a net response rate of 24.6%.…”
Section: Sample and Data Collection Proceduressupporting
confidence: 79%
See 1 more Smart Citation
“…The fact that the individuals in the sample have different occupations contributes to the generalisation of the findings and is coherent with other studies in the literature (e.g. De Jong, De Ruyter, & Lemmink, 2004;Hartline et al, 2000). We received 255 questionnaires back, of which 234 were usable, yielding a net response rate of 24.6%.…”
Section: Sample and Data Collection Proceduressupporting
confidence: 79%
“…This is particularly relevant because a one-size-fits-all approach may not be appropriate in studies of creativity since different types of problems and task demands may require a different set of skills, cognitive strategies, and motivations (Mumford, 2003). In a services setting, frontline employees are frequently responsible for the first, and often the only, interaction with the customer (Hartline, Maxham, & McKee, 2000;Lages & Piercy, 2012). Moreover, a frontline service employee spends most of the working day essentially interacting with customers.…”
mentioning
confidence: 99%
“…Employees need flexibility to adapt their behaviors to the demands of each service encounter, thereby meeting customer needs more effectively (Hartline et al, 2000). Bowen and Lawler (1992) suggest that empowerment is recommended when service delivery involves managing a relationship as opposed to simply performing a transaction.…”
Section: Nsd Process Managementmentioning
confidence: 99%
“…quota) (Hartline et al, 2000), as customers would do (Parasuraman et al, 1991). Furthermore, behavior-based evaluation encourages employee performance that is consistent with customer expectation of service quality and is particularly suited to employees with customer contact (Chebat and Kollias, 2000).…”
Section: Behaviour-based Evaluationmentioning
confidence: 99%
“…Consequently, employees may experience role conflict (an incongruity within the expectations associated with a role and which can include role overload; Singh, 2000). The problems experienced by employees, who are required to adhere to company policies, rules and regulations while simultaneously providing high standards of customer service, are well documented (Babin and Boles, 1998;Bitner et al, 1990Bitner et al, , 1994Chung and Schneider, 2002;Hartline and Ferrell, 1996;Hartline et al, 2000;Hui et al, 2004). Schneider and Bowen (1985), for example, found that employees experienced role stress, job dissatisfaction and frustration over being unable to give good service because of differences between their own and managements' perceptions of how services should be delivered.…”
Section: Role Conflict and Role Ambiguitymentioning
confidence: 99%